2009
DOI: 10.1039/b821755f
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven altitudinal molecular motors on surfaces

Abstract: A Cu(I)-catalyzed 1,3-dipolar cycloaddition was used to construct a monolayer of an altitudinal molecular motor on quartz and silicon substrates, which represents the fastest light-driven molecular motor, to date, grafted to a solid surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 37 publications
2
75
0
Order By: Relevance
“…After the evaporation of the solvent the crude product was purified by flash chromatography (SiO 2 , n-heptane : EtOAc = 7 : 1) to give 1.05 g (2.24 mmol, 62 %) of colourless oil. 1 …”
Section: Synthesis Of Compounds and Intermediatesmentioning
confidence: 99%
See 2 more Smart Citations
“…After the evaporation of the solvent the crude product was purified by flash chromatography (SiO 2 , n-heptane : EtOAc = 7 : 1) to give 1.05 g (2.24 mmol, 62 %) of colourless oil. 1 …”
Section: Synthesis Of Compounds and Intermediatesmentioning
confidence: 99%
“…The filtrate was concentrated in vacuo and purified by flash chromatography (SiO 2 , n-pentane : diethyl ether = 10 : 1) to give 86 mg (0.18 mmol, 78 %) of a purple oil . 1 …”
Section: 6-bis(dec-9-enyloxy)-27-dimethyl-23-dihydro-1h-indene-1-mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-bounded molecular switches, rotors and motors are fascinating since they can be exposed to external stimuli [4][5][6] and investigated by surface analysis methods [7][8][9][10]. Recent studies have shown that surface-bounded molecular switches and rotors can be used in experimental techniques such as scanning tunneling microscopy and spectroscopy (STM/STS) which also allow the measurement of molecular switching/rotor rates and energy barriers [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The movement and dynamics of chloromethyl-and dichloromethylsylil molecules on fused silica surfaces have been analyzed by STM [4,5,27].…”
Section: Introductionmentioning
confidence: 99%